Influencia del contexto social organizacional en el comportamiento estratégico de los gerentes intermedios y su relación con el ambiente organizacional - Lobatón Gonzales, Luis (2021)
Various investigations highlight the role that middle managers play in organizational results by studying their strategic behavior, but little is known about the factors that influence the emergence of such behaviors and their relationship with the organizational environment. Using bibliographic research, this article aims to elaborate propositions of how the organizational social context, formed between senior management and middle managers, influences the appearance of a divergent or convergent strategic behavior of middle managers in different organizational environments. The proposals are based on the theories of self-determination and of the behavior of organizations. This article proposes that the autonomy support style of senior management will be positively related to environments of uncertainty, mediated by the divergent behavior of middle managers; and that the control style will be positively related to stable environments, mediated by convergent behavior.